Distribution. E in Cricetidae - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
Distribution. E Siberia and Russian Far East (E of Lena River and Yablonoi Mts E to Chukchi Peninsula). Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 309, DOI: 10.5281/zenodo.6707142